Dosage Form for Medical Students - Lim, William K (YouTube, 2020)
An overview of the common dosage forms that the medical student will encounter in the hospital. A dose form is the physical form of the drug in which measurable doses can be given. It is necessary not only to prescribe the right drug but also the appropriate dosage form, that the patient can easily administer each dose.